Pengolahan Limbah Cair Industri Tahu Menggunakan Tanaman Typha Latifolia Dan Eceng Gondok Dengan Metode Fitoremediasi - Sungkowo, Toto Heri; Elystia, Shinta; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tahu industry is a domestic industry largely do not have sewage treatment units. Wastewater of tahu industry if directly discharged into sewers or water bodies without prior treatmentcan lead environmental pollution. This study aims to look at the ability of phytoremediation system with a combination of plants Typha latifolia and eceng gondok to determine pollutantremoval efficiency parameters, there are: COD of the water eceng gondok plant weight variation, and Hydraulic Loading Rate (HLR), in this study used a plastic tub the size of 50cm x 36cm x 31cm, the soil media with a thickness of 10cm, thickness 5cm media sand and gravel media 5cm thick. Typha latifolia plant density of 1 g / cm2, the weight variation of thewater hyacinth plant (0.5 kg; 1 kg; and 1 kg), and variations HLR (500, 750 and 1000 L /m2.hr). Optimal results were obtained in plants Typha latifolia 1 g / cm2, 1.5 kg heavy watereceng gondok and HLR 500 L / m2.hari COD 200 mg / l with an efficiency of 92.42%.Keywords: Eceng gondok, Hydraulic Loading Rate (HLR), Phytoremediation, Typha latifolia, Wastewater tahu